DO DISTRACTIONS INCREASE THE NUMBER OF PRESCRIBING ERRORS IN PAEDIATRIC INTENSIVE CARE?. Issue 8 (11th July 2014) - Johnstone, L; Sutherland, A; Hawkins, K
Abstract : Background: The safe administration of medicines and the avoidance of adverse events have been at the forefront of patient safety initiatives for many years.1 – 3 There have been many studies looking at medication and prescribing errors.4 Few studies have looked at the role of distraction of clinical staff during the writing of a prescription, in contrast to the number of studies looking at the part played by distraction of nursing staff during the administration of medicines.2 – 4 Aims: This study intended to identify relationship between distractions in the prescribing process and prescribing errors the increased likelihood of a distraction outside the designated prescribing error different forms of distractions and how they occur. Methods: This is a blinded observational study. During the study, the observer recorded 200 prescriptions. Doctors and ANPs were observed as they undertook their normal prescribing activities and any events that were interrupted or distracted were documented. Each observed action was given a unique number. All prescriptions were examined by a senior pharmacist who was blinded to the outcomes of the observer's findings. Results: Of the 200 prescriptions observed, 11 prescriptions were lost to follow-up. The total error rate was 19.6 per 100 orders which maintains consistency with previous work conducted within the department. Of those prescriptions with errors, 43% were associated with a disturbance of the prescribing process. There is a significant relationship (Chi Squared p=0.028). Of the 37 errors that occurred, 23 took place at the bedside and 8 took place at the nurses' station. Twenty six prescriptions took place at designated "prescribing areas" with 6 errors noted. The majority of errors were of no/low clinical significance. Conclusion: There is a positive relationship between the distraction and prescribing error. Both are more likely to occur if the prescription is written outside a designated prescribing area.